Identifikasi dan Manajemen Risiko untuk Mereduksi Kerentanan Pada Masyarakat - Mukhammad Fatkhullah; Muhammad Alhada Fuadilah Habib; Kanita Khoirun Nisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Vulnerability is an important aspect of national development. Failure to identify and manage vulnerabilities makes programs or policies designed by the government, companies, or non-governmental organizations run not as expected. This study aims to provide an understanding of definitions, sources and forms, identification methods, and interventions in managing risk to minimize vulnerability in the community. This study uses a systematic literature review method with inclusion criteria based on keywords: vulnerability, social risk, and social protection. The inclusion and exclusion criteria include: type of publication, year, accessibility, relevance, methodology and publication contribution. Vulnerability is a condition that makes a community easily affected by various threats. These threats consist of external risks such as the natural environment, social and demographic composition as well as internal risks such as economic conditions, physical and mental health. Both external and internal risks are closely related. Identification is carried out to map and categorize not only based on the causes and forms of vulnerability, but also on the magnitude of the impact, the number of victims and the possible losses. These data are important to determine the priority scale in determining the intervention that must be carried out. Preventive interventions are needed at low risk levels, promotive at moderate risk levels, and protective at high risk levels. If prevention, support and protection are no longer possible, transformative interventions are needed to keep communities away from crises.